Use of treated graywater for fruit irrigation in the semiarid region: Legal aspects and soil quality - Franca, Carlos Laécio Evangelista; Amorim, Miriam Cleide Cavalcante de; Olszevski, Nelci; Belém, Clérison dos Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The search for sustainable environmental processes is primordial for the world and, in semi-arid regions where freshwater resources are scarce, the search for non-conventional alternatives for water use should be intensified. Thus, the objective of this work was to evaluate, under the legal aspects of agricultural reuse and soil quality, the use of treated graywater as a water source for acerola plants cultivated in the Brazilian semiarid region. The study was conducted in the rural area of Juazeiro/Bahia with treated graywater from a family adapted biofilter composed of layers of sawdust, coarse sand, gravel and pebbles. Monthly microbiological and physical-chemical analyses of the graywater and soil analyses were performed. It is concluded that there is a diversity of parameters and limit values that makes the interpretation and legal framework of graywater for irrigation difficult, with no single regulation. The greywater promoted an improvement in the chemical quality of the soil, with a decrease in the availability of Al and an increase in the Ca, Mg and P contents. The reuse of greywater for irrigation met the environmental and sustainability criteria by not being discharged directly into the soil and by being used for a noble purpose such as the irrigation of agricultural crops. However, it is necessary to have a legal regulatory unification at the national level, which establishes standards and guidelines for the practice of graywater reuse.